Quantum optimization in autonomous underwater vehicle routing navigation - Xuan Kien, Dang; Vu, Ngoc-Ha (Journal of Transportation Science and Technology, 2025)
Quantum optimization is currently developing strongly in many research fields. This method uses the principle of quantum mechanics to determine the process of quantum fluctuations in optimal calculations. In this study, we use the Quantum Annealing Algorithm (QAA) to optimize the journey of the Autonomous Underwater Vehicle (AUV) to find the shortest distance, consume the least energy, and even avoid obstacles while moving. The research results on simulations are compared with the traditional Dijkstra method to evaluate the effectiveness of the proposed method, thereby affirming the superiority of quantum optimization in the automatic control of AUV.